Modal Pengetahuan Situs Pusaka Budaya Pesanggrahan Pakubuwono IX Langenharjo dan Pengembangan Potensi Wisata - Agustian Budi Prasetya; Puji Wahono; GPH Surya Witjaksono (IKRAITH-EKONOMIKA, 2023)
The paper discusses about knowledge assets that applied in heritage site . It is identified the knowledge resources of the site, that suppose to be retained by involving five stakeholders at estate of King PB IX at Sukoharjo City. The research utilizes desk research methodes, obeservation, ingterview and literature study. The paper describe analytically knowledge and phisical assets of the heritage estage and pentahelix model.The paper found that along with effort to maintain the knowledge capital, the heritage estate, might call for involvement in heritage stakeholders to share and collaborate each other. Otherwise the estate might under value of its knowledge capital and loss the opportunity to be creative tourism destination.